A Natural Diels‐Alder Biocatalyst Enables Efficient [4+2] Cycloaddition Under Harsh Reaction Conditions. Issue 20 (30th September 2019) - Marsh, Carl O.; Lees, Nicholas R.; Han, Li‐Chen; Byrne, Matthew J.; Mbatha, Sbusisiwe Z.; Maschio, Laurence; Pagden‐Ratcliffe, Sebastian; Duke, Phillip W.; Stach, James E. M.; Curnow, Paul; Willis, Christine L.; Race, Paul R.
Abstract: Carbon‐carbon bond formation is a fundamental transformation in both synthetic chemistry and biosynthesis. Enzymes catalyze such reactions with exquisite selectivity which often cannot be achieved using non‐biological methods but may suffer from an intolerance of high temperature and the presence of organic solvents limiting their applications. Here we report the thermodynamic and kinetic stability of the β ‐barrel natural Diels‐Alderase AbyU, which catalyzes formation of the spirotetronate core of the antimicrobial natural product abyssomicin C, with creation of 3 new asymmetric centers. This enzyme is shown to catalyze [4+2] cycloadditions at elevated temperature (up to 65 °C), and in the presence of organic solvents (MeOH, CH3 CN and DMSO) and the chemical denaturant guanidinium hydrochloride, revealing that AbyU has potential widespread value as a biocatalyst. Abstract : Feel the burn : Exploration of the thermodynamic and kinetic stability of the natural Diels‐Alderase AbyU establishes the operational limits of this biocatalyst, revealing the enzyme's capacity to catalyze [4+2] cycloadditions under harsh reaction conditions.